Evaluation of Genetic Diversity in Cardiospermum halicacabum based on Geographical Variation Using RAPD Markers - A, Annamalai; V.L, Christina; P.T.V., Lakshmi (Pharmacognosy Communications)
Background: Genetic diversity at the intra species level arises from differences in climatic conditions, geographical distribution and environmental stress. Thus the study of genetic diversity assists in determining the phylogeny of a particular plant species and the impact of geographical locations on the plant genome. Objective: To assess the genetic diversity and phylogeny of Cardiospermum halicacabum species’ from different regions within the state of Tamil Nadu in India. Materials and Methods: Plant DNA was isolated and amplified using eight random primers. The presence of amplified DNA bands was recorded as a 1, while the absence of any bands was recorded as a 0. The percentages of polymorphism were determined using the ratio of similarity to dissimilarity of band pattern. The data was analysed using the VisionWork LS Analysis Software to construct a dendrogram to create a phylogenetic tree, for cluster analysis using UPGMA (Unweigthed Pair Group Method with Arithmetical Mean). Results: RAPD analysis showed varied amplifications for each sample. The polymorphism was 29.41% and the number of polymorphic fragments ranged from 603 bp to 6557 bp. The dendrogram revealed two clusters, Cluster I included the sample from Chennai, while Cluster II included samples from Dharmapuri, Thanjavur, Thirunalveli, Coimbatore and Madurai, thus showing the extent of intraspecific variation. Conclusion: Variation in geographical plant location was consistent with genetic differences. Therefore DNA banding patterns may be used as a fingerprint marker for the identification of Cardiospermum halicacabum species.
Keywords: Genetic diversity; RAPD; phylogenetic tree; Cardiospermum halicacabum